Comparison of Vitamin D, Interleukin-6, And Interleukin-8 Levels in Covid Positive patients With or Without Cytokines Storm - Aneela Amjad, Sidra Manzoor, Syeda Zahra Wasti, Zeeshan Shoukat, Syeda Khadija Kazmi, Umer Ilyas, Tania Shakoori, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Currently world is within the clutches of the coronavirus disease (COVID-19) , caused by the SARS-CoV-2 virus, COVID-19 virus has evolved to human-to-human spread . COVID-19 infection can cause fever, fatigue, dry cough, severe pneumonia, respiratory distress syndrome and in some instances death. Release of cytokine is the main process by which COVID-19 affects human system. High level of chemokines and pro-inflammatory cytokines has been observed among the patients with COVID-19. Methodology: 100 COVID-19 positive patients with cytokine storm and100 COVID-19 positive patients without cytokine storm with 18+ age and both gender were included after their formal consent. Interleukin-6, interleukin-8 and Vitamin-D were determined by their respective ELISA kits. SPSS software was applied for statistical analysis. Results: the results of current study showed the raised levels of interleukin-6 and interleukin 8 in case group as compared to controls. Levels of Vit D were compromised in case of Covid patients with cytokine storm than controls respectively. Conclusion: it was concluded that increased oxidative stress and lacking anti-oxidants may add to the development and advancement of cytokine storm in corona virus positive patients.